The association between stressful life events and depressive symptoms among Cypriot university students: a cross-sectional descriptive correlational study - Middleton, Nicos; Merkouris, Anastasios; Karanikola, Maria; Sokratous, Sokratis (My University, 2013)
Background: Previous findings suggest that stressful life events have a causal relationship with depressive symptoms. However, to date little is known concerning the contribution of the number and severity of recent stressful life events on the prevalence of depressive symptoms among university students. The aim of this study was to investigate the prevalence of depressive symptoms and its association with the number and the severity of self-reported stressful life events among university students in Cyprus. Methods: A descriptive correlational design with cross sectional comparison was used. The CES-D scale was applied for the assessment of depressive symptoms and the LESS instrument for stressful life events. Both scales were completed anonymously and voluntarily by 1.500 students (response rate 85%). Results: The prevalence of mild to moderate depressive symptoms [CES-D score between 16 and 21] and of clinically significant depressive symptoms [CES-D score ≥ 22] were 18.8% and 25.3% respectively. There were statistically significant differences in clinically significant depressive symptoms by gender, with higher rates among women (x2 = 8.53, df = 1, p = 0.003). Higher scores on the LESS scale were associated with more frequent reports of clinical depressive symptoms (x2 = 70.63, df = 4, p < 0.001). Similarly, an association was found between the number of life events and clinical depressive symptoms (x2 = 40.06, df = 4, p < 0.001). Logistic regression analysis after adjusting for socio-demographic characteristics confirmed that the responders who reported a high number (n = 12–21) of stressful life events during the previous year (OR = 2.64 95% CI: 1.02, 6.83) and a severe degree of stress due to these events (total LESS score > 351, OR = 3.03 95% CI: 1.66, 5.39) were more likely to manifest clinical depressive symptoms. Conclusions: The high frequency of occurrence of depressive symptoms among Cypriot university students, as well as the strong association with stressful life events, highlights the need for psychological empowerment strategies towards students by institutional counseling services.
Investigation of stressful life events as significant predictors on depressive symptoms among Cypriot University students: a cross-sectional descriptive correlational study.
Keywords: Center for epidemiology studies (CES-D); Depression; Life events scale for students (LESS); Stressful life events; Cypriot university students